Estratégias e estruturas de trade marketing na indústria de bens de consumo não-duráveis como resposta às transformações ocorridas no varejo alimentício do Brasil - Motta, Rodrigo Guimarães (2007)
The main distribution channel for non-durable consumer goods is the food retail, which is composed of bars, mini markets, bakeries, convenience stores, supermarkets and hypermarkets. In order to sell to these customers, the industries had a marketing department formed by product managers and a sales department that had regional and key account managers. Without bargain power, the retailers had to accept the negotiation terms presented by the industries that possessed strong brands. Through an exploratory-descriptive study made with twenty industries with an income over R$ 100 million per year, this dissertation has found changes that have occurred with the brazilian retailers, namely the globalization of the supermarket chains, the consolidation of the supermarkets, the arrival of new retail models, the strengthening of private labels, the competition of retailers of different formats and the expansion of the on line retail. In this new scenario, the retailers demand better discounts and more services from the industries that ended up loosing profitability. To overcome such losses the industries are now implementing the so called trade marketing department, that aims at adequating the strategy, the structure and the operation to the distribution channel dynamics in such a way customers and consumers are satisfied, in a profitable way to the industry. This paper ends with trade marketing strategies, structures and perspectives in Brazil